A whole person approach to wellbeing building sense of safety - Lynch, Johanna (Routledge, an imprint of the Taylor & Francis Group, 2021)
"This book builds on the person-centred medicine movement to promote a shift in the philosophy of care of distress. It discusses the vital importance of whole person health, healing and growth. Developing a new transdisciplinary concept of 'sense of safety', this book argues that the whole person needs to be understood within their context and relationships, and explores the appraisal and coping systems that are part of health. Using clinical vignettes to illustrate her argument, Lynch draws on an understanding of attachment, and trauma-informed approaches to life story, and counsels against an over-reliance on symptom-based fragmentation of body and mind. Integrating literature from social determinants of health, psychology, psychotherapy, education and the social sciences with new research from the fields of immunology, endocrinology and neurology, this broad-ranging book is relevant to all those with an interest in person-centred healthcare, including academics and practitioners from medicine, nursing, mental health and public health."--Provided by publisher.